Psychological wellbeing, family cohesion, and purposeful life in male prisoners: A cross-sectional study - Ghazanfari, Hooshang; Miri, Sakineh; Taebi, Mozhgan; Farokhzadian, Jamileh (Frontiers in Psychiatry, 2023)
Background: Psychological well-being, family cohesion, and purposeful life are important determinants of the prisoners’ overall well-being and health; therefore, their evaluation is extremely important in prisoners as a vulnerable group. Objective: This study evaluated psychological well-being, family cohesion, purposeful life, and their correlations in male prisoners. Methods: This cross-sectional study used simple random sampling to select 259 male prisoners. Data were collected using questionnaires of Ryff psychological well-being, Fischer family cohesion, and Crumbaugh & Maholick purpose in life. Results: Majority of (78%) the participants were 20-40 years old and married (59%). The mean scores of psychological well-being, family cohesion, and purposeful life of the male prisoners were moderate. Psychological well-being was directly correlated to family cohesion in male prisoners, but it had no significant correlation with a purposeful life. Family cohesion was not significantly correlated to a purposeful life. Conclusion: Regarding the moderate level of psychological well-being in prisoners, it is suggested to pay more attention to educational and supportive programs in prisons for promoting such indicators in prisoners.